Quantitative description of the relationship between the enhancement of distraction-suppression and brain local state alteration after transcranial direct current stimulation - Zhang, Di; Liu, Jiaojiao; Fan, Li; Liu, Qiang (Frontiers in Neuroscience, 2022)
Anodal transcranial direct current stimulation (tDCS) over the left dorsal lateral prefrontal cortex (lDLPFC) can improve distraction suppression ability, possibly by distantly regulating the connection properties of several large-scale brain networks and local brain state changes. However, little is known about the local state alteration that tDCS can induce in distant but task-related regions and the relationship between performance enhancement and local state alteration in potentially related regions, resulting in inefficient and uncertain tDCS regulation. We aimed to examine the alteration of brain local state before and after tDCS and its relationship with performance enhancement. With the within-subject design, the participants received anodal (1.5 mA) and sham tDCS at F3 (lDLPFC) for 20 min. The visual search task and resting-state functional magnetic resonance imaging (rsfMRI) were performed before and after stimulation. Anodal tDCS significantly enhanced distraction suppression. The amplitude of low-frequency fluctuation (ALFF) in the left parietal region significantly decreased, the decrement significantly positively correlated with performance enhancement after anodal tDCS. As well, the regional homogeneity (ReHo) in the left precuneus significantly increased, and the increasement significantly positively correlated with performance enhancement. Anodal tDCS over the lDLPFC can distantly modulate the local state of the brain and improve the distraction suppression ability. These two aspects are closely related and provide a direct and efficient approach to enhancing performance.